Advances in the Electronics for Cyclic Voltammetry: the Case of Gas Detection by Using Microfabricated Electrodes - Pennazza, Giorgio; Santonico, Marco; Vollero, Luca; Zompanti, Alessandro; Sabatini, Anna; Kumar, Nandeesh; Pini, Ivan; Quiros Solano, William F.; Sarro, Lina; D'Amico, Arnaldo (Frontiers in Chemistry, 2018)
This paper presents an advanced voltammetric system to be used as electronic tongue for liquid and gas analysis. It has been designed to be more flexible and accurate with respect to other existing and similar systems. It features improved electronics and additional operative conditions. Among others these include the possibility to optically excite the solution and to treat the output signal by a differentiation process in order to better evidence the existence of small details in the response curve. Finally by the same type of tongue preliminary results are shown dealing with O2 and CO2 concentration measurements in appropriate solutions.